Statistical analysis of Ethno-veterinary plants from Bhil, Pawra, Tadvi and Korku tribes of Buldhana district, Maharashtra: A benevolence for health of native animals (International Journal of Food and Nutritional Sciences, 2022)
The tribal communities like Bhil, Pawra, Tadvi and Korku are gold mines of traditionalveterinary knowledge as they have been using plants to keep their livestock healthy andfree from diseases. Several factors of modern civilization day by day is getting diminishedthis knowledge.